Measurement of the inclusive J/$$ψ $$ ψ polarization at forward rapidity in pp collisions at $$\mathbf {\sqrt{s} = 8}$$ s=8 TeV - S. Acharya (European Physical Journal C: Particles and Fields, 2018)
Abstract We report on the measurement of the inclusive J/$$ψ $$ ψ polarization parameters in pp collisions at a center of mass energy $$\sqrt{s} = 8$$ s=8 TeV with the ALICE detector at the LHC. The analysis is based on a data sample corresponding to an integrated luminosity of 1.23 pb$$^{-1}$$ -1 . J/$$ψ $$ ψ resonances are reconstructed in their di-muon decay channel in the rapidity interval $$2.5< y < 4.0$$ 2.5<y<4.0 and over the transverse-momentum interval $$2< p_T < 15$$ 2<pT<15 $$GeV/c$$ GeV/c . The three polarization parameters ($$λ _θ $$ λθ , $$λ _φ $$ λφ , $$λ _{θ φ }$$ λθφ ) are measured as a function of $$p_T$$ pT both in the helicity and Collins-Soper reference frames. The measured J/$$ψ $$ ψ polarization parameters are found to be compatible with zero within uncertainties, contrary to expectations from all available predictions. The results are compared with the measurement in pp collisions at $$\sqrt{s} = 7$$ s=7 TeV.